Izbor gradiva za Slovensko bibliografijo - Šušterčič, Marjeta (Knjižnica, 2010)
Selection principles are an important stage in the creation of a national bibliography. The article outlines the selection of the national output to be included in Slovenian bibliography. It also presents theoretical basis for selection in general, with the emphasis on international guidelines and on the development of national principles and professional outlines. Statistical data and examples give more detailed analysis of selection criteria of articles regarding different types of serial publications. Results of the study show that selection criteria for Slovenian bibliography are to be constantly verified due to the dynamics of the national publishing industry. Nevertheless, the main features of selection criteria remain unchanged: lasting value of subject matter with the emphasis on scientific research and expert knowledge.
Keywords: nacionalne bibliografije; Slovenska bibliografija; izbor gradiva; kriteriji; članki